Accent-induced bias in linguistic transcriptions. (November 2019) - Sloos, Marjoleine; Ariza García, Andrea; Andersson, Alexandra; Neijmeijer, Mathea
Abstract: Many linguistic analyses rely on phonetic transcriptions. Two factors that might affect the accuracy of transcriptions are perceived accent and the listener's linguistic knowledge about that accent. This article focuses on the susceptibility of transcribers to such accent-induced bias, based on speaker's accent, transcriber's variety, and the transcriber's knowledge about the language variety they are transcribing. We offer a method to statistically detect accent-induced biases in linguistic transcriptions. This article investigates accent-induced bias in transcriptions of Reference French and Laurentian French (in Canada). In Reference French, high front vowels are phonologically tense /i y/, but they may be phonetically realised as lax [ɪ ʏ ]. In Laurentian French, lax [ɪ ʏ ] occur as allophones of /i y/. We compare transcriptions of different groups of coders: native speakers of Reference French, native speakers of Laurentian French, and advanced L2 learners of French who are native speakers of Dutch. Half of the Dutch group was informed about the native variety of the speakers and the other half was not. Results show that perceived accent among the native transcribers is a relatively strong predictor for transcribed sounds. In addition, the Dutch transcribers who were informed about the speaker's variety transcribed more lax vowels in Laurentian French and more tense vowels in Reference French than the Dutch transcribers who were not informed. Native transcribers also showed contextual effects related to the allophonic distribution of the vowels in Laurentian French. These results are indicative of accent-induced bias. The results are analysed in a predictive top-down model to explain the effect of prior experience and information about the language variety in speech perception. Highlights: Perceived variety is the main transcription bias among native speakers. Phonological context influences transcription among native speakers. Subtle information about the speakers' variety influences transcriptions of non-native coders.